THE IMPACT OF INTERACTION ON SECOND-LANGUAGE ACQUISITION AND LISTENING - Michael Amankwaa Adu; Levina N. Abunya; Edward Owusu; Gifty Budu (Journal of Languages for Specific Purposes)
The interaction hypothesis of second-language acquisition states that the development of language proficiency can be facilitated by face-to-face interaction and communication between native speakers of the language and language learners. This paper examines the relationship between interaction and listening of learners in the second language classroom. The study compared the comprehension of 8 non-native English speakers in a Ghanaian junior high school on directions to a listening comprehension task presented by a proficient speaker of English. The learners were divided into one experimental group and one control group and compared under two input conditions: pre-modified input, in which the proficient speaker presents the tasks using language that has been modified by decreased complexity, increased quantity, and redundancy; and interactionally modified input, in which the tasks are presented using language that had not been pre-modified but had enough opportunities for interaction with the proficient speaker. The study found that repeating and rephrasing the language to explain the directions during interaction resulted in increased comprehension. The study’s findings support longstanding claims about the importance of interaction in promoting second-language listening comprehension. These findings also provide recommendations for reorganizing classroom interaction to meet learners’ needs for comprehensible input.